2006
DOI: 10.3126/jnbs.v1i1.43
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Performance of Securities Market in Nepal

Abstract: Securities Board, Nepal, an apex regulator and facilitator of capital market, and Nepal Stock Exchange Ltd., only a single stock market, are the main constituents of securities market in Nepal. This paper attempts to study the growth trend and analyze the performance of Nepalese securities market. Likewise, the variables such as number of listed and traded companies and their securities, number of transactions, trading turnovers, paid up value, market capitalization and NEPSE index are analyzed for the seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…They also found unidirectional causality runs from stock market development to economic growth in Nepal. Similarly, Gurung (2004) revealed that NEPSE index growth rate was very low and highly fluctuating that indicates poor performance of public limited companies listed in stock exchange. Such erratic trend in the value of market capitalization and its low contribution to GDP indicated the poor and immature capital market, de-motivation in investment in the companies, and downward trend of economy during the study period.…”
Section: Review On Secondary Capital Marketmentioning
confidence: 99%
See 3 more Smart Citations
“…They also found unidirectional causality runs from stock market development to economic growth in Nepal. Similarly, Gurung (2004) revealed that NEPSE index growth rate was very low and highly fluctuating that indicates poor performance of public limited companies listed in stock exchange. Such erratic trend in the value of market capitalization and its low contribution to GDP indicated the poor and immature capital market, de-motivation in investment in the companies, and downward trend of economy during the study period.…”
Section: Review On Secondary Capital Marketmentioning
confidence: 99%
“…Second, it is presumed to include companies' past retained profits and future growth prospects so that a higher ratio to GDP can signify growth prospects as well as stock market development (Levine & Zervos, 1998;Rajan & Zingales, 2003). Gurung (2004) Al-Tamimi (2006) suggested that expected corporate earnings, get rich quick, stock marketability, past performance of the firm's stock, government holdings and the creation of the organized financial markets to be the most influencing factors on the UAE investor behavior. Similarly, Akbar et al (2016) proved that advocate recommendations, self-image/firm image coincidence, neutral information have positive significant relationship with individual investor investment decision whereas, the study did not find any evidence on relationship between accounting information, classical wealth maximization and personal financial needs.…”
Section: The Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…It saves the company enormously of the hassles of capital issue (Gurusamy, 2011). Gurung (2004) carried a study on growth and performance of securities market in Nepal and concluded that the primary market is poor in case of public issue in Nepal. He further stated this poor trend indicates public response on the liberalization and public participation policies of the government became ineffective except in a few sectors.…”
Section: Theoretical Frameworkmentioning
confidence: 99%